Interrelationship among body mass index, body composition, and biochemical profiles of overweight adolescents in south of Brazil: A cross-sectional study. - Marielle Priscila de Paula Silva Lalucci; Déborah Cristina de Souza Marques; Isabella Caroline Santos; Jéssica Zirondi Caitano; Bruno Ferrari Silva; Pablo Valdés-Badilla; Braulio Henrique Magnani Branco (Nutrición Clínica y Dietética Hospitalaria, 2023)
Introduction: Obesity in adolescence is associated with severe health complications. Objective: To analyze possible associations among body mass index (BMI), body composition, and biochemical profiles of overweight or obese adolescents. Methods: The study was carried out between 2017 and 2020 and included 132 adolescents aged 10 to 18 years. The following variables were analyzed: BMI, fat-free mass (FFM), body fat mass (BFM), skeletal muscle mass (SMM), body fat percentage (%BF), waist-to-hip ratio (WHR), lean mass index (LMI), fat mass index (FMI), and fat-to-lean mass ratio (FMR), as well as total cholesterol (TC), high-density lipoprotein (HDL-c), low-density lipoprotein (LDL-c) and glutamic-oxaloacetic transaminase (TGO). Statistical analyses were performed using SPSS® version 20.0, considering p<0.05 as significant. Results: Higher values were identified for height, LBM, FFM, and SMM in the male group. On the other hand, higher values were identified for the %BF and FMI in the female group. The female, male, and general groups showed significant correlations between BMI and FMR (r = 0.69, 0.74, and 0.69, respectively), BMI and FFM (r = 0.44, 0.67, and 0.49, respectively), BMI and SMM (r = 0.44, 0.68, and 0.50, respectively), and BMI and %BF (r = 0.40, 0.54, and 0.47, respectively). In the general group, BMI and HDL levels were correlated (r = −0.18; p=0.04). The BFM and WHR showed a predictive effect for TC; WHR and %BF showed a predictive effect for LDL concentrations, and %BF had a predictive effect for TGO (p<0.05). Conclusions: It was possible to verify that BMI, body composition, and biochemical measures show an interrelationship between them, such as with a worsening of anthropometric and body composition indicators associated with worst biochemical parameters, e.g., lower HDL-c and higher TC, LDL-c, and TGO. Thus, public policies are indispensable for combating obesity and related comorbidities in the early phases of life.